Design and implementation of malay digit speech recognizer - 257901 Hong, Kai Sze; Sheikh Hussain Shaikh Salleh, 1958-; Ahmad Zuri Sha'ameri; Malaysian Science and Technology Congress (2002 : Genting Highlands, Pahang) (Skudai : Universiti Teknologi Malaysia, 2002)
16